20‐hydroxyecdysone mediates non‐canonical regulation of mosquito vitellogenins through alternative splicing. Issue 4 (10th April 2014) - Provost‐Javier, K. N.; Rasgon, J. L.
Abstract Vitellogenesis is one of the most well‐studied physiological processes in mosquitoes. Expression of mosquito vitellogenin genes is classically described as being restricted to female adult reproduction. We report premature vitellogenin transcript expression in three vector mosquitoes: Culex tarsalis, Aedes aegypti and Anopheles gambiae. Vitellogenins expressed during non‐reproductive stages are alternatively spliced to retain their first intron and encode premature termination codons. We show that intron retention results in transcript degradation by translation‐dependent nonsense‐mediated mRNA decay. This is probably an example of regulated unproductive splicing and translation (RUST), a mechanism known to regulate gene expression in numerous organisms but which has never been described in mosquitoes. We demonstrate that the hormone 20‐hydroxyecdysone (20E) is responsible for regulating post‐transcriptional splicing of vitellogenin. After exposure of previtellogenic fat bodies to 20E, vitellogenin expression switches from a non‐productive intron‐retaining transcript to a spliced protein‐coding transcript. This effect is independent of factors classically known to influence transcription, such as juvenile hormone‐mediated competence and amino acid signalling through the target of rapamycin pathway. Non‐canonical regulation of vitellogenesis through RUST is a novel role for the multifunctional hormone 20E, and may have important implications for general patterns of gene regulation in mosquitoes.